Modulation of Neurogenesis through the Promotion of Energy Production Activity Is behind the Antidepressant-Like Effect of Colonial Green Alga, Botryococcus braunii - Sasaki, Kazunori; Othman, Mahmoud B.; Demura, Mikihide; Watanabe, Makoto; Isoda, Hiroko (Frontiers in Physiology, 2017)
Algae have been recognized as important resources providing functional components due to their capacity to exert beneficial effects on health. Therefore, there is increasing interest in investigating the biological activity of algae. In this study, we evaluated the antidepressant-like effect of the administration of 100 mg/kg/day of the ethanol extract of colonial green alga Botryococcus braunii (EEB) for 14 consecutive days in the forced swimming test (FST)-induced depression in imprinting control region (ICR) mice. Imipramine, a commercial antidepressant drug, was used as a positive control. In addition, we investigated the molecular mechanisms underlying the effect of EEB by measuring ATP production and by assessing any change in gene expression at the end of the treatment using real-time polymerase chain reaction (PCR) and microarray assays. We showed that the immobility time in the water-administered control (FST stress) group gradually increased from day 1 to day 14. However, treatment with EEB caused a significant decrease of immobility time in the FST compared with that in the FST stress group. Microarray and real-time PCR results revealed that EEB treatment induced variation in the expression of several genes associated with neurogenesis, energy metabolism, and dopamine synthesis. Interestingly, we revealed that only EEB treatment enhanced the promotion of energy production, while treatment with imipramine was ineffective. Our study provides the first evidence that B. braunii enhances energy production, which may contribute to the modulation of neurogenesis and to the enhancement of dopaminergic function, in turn potentially underlying the antistress- and antidepressant-like effects that we observed.